Arctic Biodiversity Data Service Progress report: 2017-2019 - Conservation of Arctic Flora and Fauna (CAFF) (Arctic Council Secretariat, 2019)
Progress report 2017-2018. The ABDS is the online, interoperable data management system for biodiversity data generated via the Conservation of Arctic Flora and Fauna (CAFF), the Arctic Council’s biodiversity working group. Its goal is to facilitate access, integration, analysis and display of biodiversity information for scientists, practitioners, managers, policy makers and others working to understand, conserve and manage the Arctic's wildlife and ecosystems.